LEADERSHIP IN THE STUDENT COLLECTIVE - ZHUKOVA, Anna R. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2021)
Objective. The aim of the article is to study the phenomenon of leadership in the student collective. Methods. During the research and to achieve its goal, theoretical research methods were used, including analysis and synthesis, generalization, explanation. Results. As a result, the problems of formation of leadership qualities in students of higher education institutions are analyzed, the development history of the leadership problem, the versatility of the concept are considered. Interpretations of the leadership phenomenon existing in domestic and foreign literature are presented. The phenomenon of the leadership role differentiation in a group is analyzed, the role of libraries in the formation of students’ leadership competence is highlighted. Conclusion. The conclusion indicates that for the effective formation of students’ leadership qualities it is necessary to study their psychological characteristics and that libraries play a significant role in the process of formation of students’ leadership qualities.